Оцінка стану рослин Catalpa bignonioides Walt. та C. speciosa Ward. в умовах придорожньої лісосмуги - Nemchenko, M.V.; Bessonova, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The state of plants of Catalpa bignonioides Walt. and Catalpa speciosa Ward. in two-layer afforestation along Zaporozhya highway was estimated. It was established changes of some morphological characteristics of shoots and leaves in this ecological condition.